The Role of Family Functioning in the Quality of Life of Internet-Addicted Generation Z Individual - Riyanto, Melvin Adrian; Roswiyani, Roswiyani; Satiadarma, Monty P. (GoAcademica Research & Publishing, 2025)
The rapid development of information technology and internet access has significantly impacted Generation Z, the largest group of internet users in Indonesia. While the internet provides various benefits, excessive use may lead to internet addiction, negatively affecting quality of life, particularly in psychological, physical, and social domains. Family functioning plays a crucial role in supporting the well-being of individuals experiencing internet addiction. This study aims to examine the effect of family functioning on the quality of life of Generation Z individuals with internet addiction. A quantitative approach was employed involving 633 participants aged 17-27 years who were categorized as having moderate to severe internet addiction. Measurements were conducted using the Internet Addiction Test (IAT) by Young (1998), WHOQOL-BREF by the World Health Organization (1996), and the McMaster Family Assessment Device-General Functioning (FAD-GF) by Epstein, Baldwin, & Bishop (1983). Data were analyzed using Pearson correlation and linear regression. The results revealed a significant negative correlation between family functioning scores and quality of life, indicating that better family functioning (lower FAD-GF scores) is associated with higher quality of life. Family functioning contributed most to the social domain (r = -.299, R² = .099, p < .001), followed by the environmental (r = -.275, R² = .081, p < .001), psychological (r = -.234, R² = .061, p < .001), and physical dimensions (r = -.161, R² = .031, p < .001). These findings emphasize the importance of family functioning particularly emotional and social support in enhancing the quality of life among Generation Z individuals with internet addiction.